Vectorial On‐Surface Synthesis of Polar 2D Polymer Crystals - Takahiro Kojima; Karan Patel; Shunpei Nobusue; Ahmed Mahmoud; Cong Xie; Takahiro Nakae; Shigeki Kawai; Kazuhiro Fukami; Hiroshi Sakaguchi (Advanced Materials Interfaces, 2023)
Abstract The asymmetric introduction of functional groups into polymers is promising due to its potential to provide novel electronic and magnetic properties. Though traditional on‐surface bottom‐up synthesis has succeeded in creating various types of polymers, it struggles at realizing asymmetry due to the difficulty of stereoregular polymerization and the tendency for overall polarity cancellation during agglomeration. Here, enabled by the low halogen‐contaminated metal surfaces provided by two‐zone chemical vapor deposition, “compass” precursors possessing three independent bonding, edge, and dipole vectors undergo isotactic polymerization via the vectorial self‐assembly of chiral precursor diradicals without the need for chiral catalysts required in conventional in‐solution polymerization. The isotactic polymers exhibit polar 2D crystalline structures due to the hetero‐edge CH–π interaction between the standing phenyl and butoxy group surpassing the homo‐edge interactions of π–π and CHCH. The developed vectorial on‐surface synthetic technique not only paves the way to the realization of stereoregular control but also unlocks unprecedented crystal engineering.